Role overload, leader facilitation, workgroup support, employee recognition and turover intention among lecturers in private university colleges in Negeri Sembilan - Darishinee, Balasingam (2017)
Retaining talented lectures in Private Higher Education Institutions (PHEI) become an alarming issue for the PHEI’s managements. Lectures face many difficulties in private higher education institutions compare to public higher education institutions. Some scholars have come up with several factors that could provide the impact on turnover intention. However, studies on the impact of role overload, leader facilitation, workgroup support and employee recognition towards turnover intention specifically among PHEIs’ lectures were very limited. The objective of this study is to identify the role overload, leader facilitation, workgroup support and employee recognition that affect turnover intention among PHEIs lectures in Negeri Sembilan. Research data were obtained from two PHEIs in Negeri Sembilan; Inti International University Nilai and KTG Education Group in Mantin. Total five hypotheses were developed in this study. The quantitative research design used to collect the data. Information was collected through questionnaires and was analyzed by using Statistical Package for Social Science (SPSS) version 16.0. Total 152 respondents were involved in this study. Cross sectional research method has been used to synthesis less biased and more accurate result. This research applied descriptive statistics, reliability analysis and inferential analysis to determine the relationship among the variables. Based on the correlation analysis, it has found that role overload and turnover intention shows a positive relationship (r = .725**, p ≤ 0.01). Meanwhile, leader facilitation (r = -.669**, p ≤ 0.01), workgroup support (r = -.750**, p ≤ 0.01) and employee recognition (r = -.801**, p ≤ 0.01) shows negative relationship. The coefficient of determination value (R2 = 0.709) and indicated that role overload, leader facilitation, workgroup support and employee recognition have contributed 70% to the lecturers’ turnover intention in PHEI in Negeri Sembilan. Based on multiple regression analysis result, it has found that employee recognition (β -.420, p ≤0.00) has the most significant relationship and reported as high contributor for employee turnover intention. Meanwhile, the second highest contributing factor is role overload (β .232, p ≤0.04 ) and following by workgroup support (β -. 195, p ≤0.17). The factor that least contributed for employee turnover intention among (PHEI) in Negeri Sembilan is leader facilitation (β -.086, p ≤0.246). This research study has come up with appropriate suggestions for the (PHEI) management and insights for future researchers and for better researches. This research had fulfilled the objectives set earlier by the researcher.